2015
DOI: 10.1017/s0022377815000446
|View full text |Cite
|
Sign up to set email alerts
|

Trapped-electron runaway effect

Abstract: In a tokamak, trapped electrons subject to a strong electric field cannot run away immediately, because their parallel velocity does not increase over a bounce period. However, they do pinch towards the tokamak center. As they pinch towards the center, the trapping cone becomes more narrow, so eventually they can be detrapped and run away. When they run away, trapped electrons will have very a different signature from circulating electrons subject to the Dreicer mechanism. The characteristics of what are calle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Given that electrons with large pitch angle are less susceptible to the electric force acceleration, they more easily lose energy and return to the thermal population. In tokamaks this effect can be further enhanced by the inhomogeneity of magnetic field, since electrons with large pitch angle become trapped electrons and will not be further accelerated [31].…”
mentioning
confidence: 99%
“…Given that electrons with large pitch angle are less susceptible to the electric force acceleration, they more easily lose energy and return to the thermal population. In tokamaks this effect can be further enhanced by the inhomogeneity of magnetic field, since electrons with large pitch angle become trapped electrons and will not be further accelerated [31].…”
mentioning
confidence: 99%
“…There can, however, exist superthermal electrons with p > p crit that are poloidally trapped. In fact, such REs are generated in significant numbers during the avalanche [35,36,37]: thermal electrons lifted to the RE regime via knock-on collisions can have large p ⊥ causing them to become poloidally trapped when they are born off-axis. Also during the hot-tail generation the initial fast electron population is isotropic.…”
Section: Transport Of Poloidally Trapped Runaway Electronsmentioning
confidence: 99%
“…As such, a possibility exists that they remain confined even if the plasma becomes momentarily stochastic and passing RE inventory is lost. When flux surfaces are reformed, some of the surviving trapped REs could turn to passing orbits via collisional scattering or Ware pinch [36] and provide a new RE seed.…”
Section: Transport Of Poloidally Trapped Runaway Electronsmentioning
confidence: 99%
“…When trapped, the electron will not run away further because of the cancellation between the acceleration and deceleration of E in forward and backward motion, and will loose energy due to collisions and radiation damping. In previous studies it has been shown that the trapping of REs can reduce the avalanche growth rate [24]. In order to take into account the bounce motion of runaway electrons, we have modified the QUADRE code to use a bounce-average kinetic equation which is similar to that in Ref.…”
Section: Kinetic Model Of Runaway Electronsmentioning
confidence: 99%